2016
DOI: 10.5152/jtgga.2016.16112
|View full text |Cite
|
Sign up to set email alerts
|

Are adipokines associated with gestational diabetes mellitus?

Abstract: Conclusion:No differences were found in serum chemerin, RBP-4, and visfatin between pregnant women with GDM and healthy pregnant women. Further prospective studies will be essential to elucidate the contribution of adipokines to GDM and the positive correlation between maternal RBP-4 and chemerin. (J Turk Ger Gynecol Assoc 2016; 17: 186-90) Keywords: Chemerin, retinol binding protein-4, visfatin, gestational diabetes Received: 13 July, 2016 Accepted: 15 October, 2016 Are adipokines associated with gesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 41 publications
0
18
0
1
Order By: Relevance
“…Of the 494 articles that were retrieved, 20 were included in the meta-analysis; four were apelin studies [4,6,7,11], nine were chemerin studies [5,8,15,16,[23][24][25][26][27], five were omentin studies [28][29][30][31][32], one study involved both apelin and omentin [12], and one study involved both chemerin and omentin [33]. The 20 studies enrolled 2981 participants, of which 1493 were GDM patients and 1488 were healthy pregnant women (controls) [4-8, 11, 12, 15, 16, 23-33] (Fig.…”
Section: Literature Research and Characteristics Of The Included Studiesmentioning
confidence: 99%
“…Of the 494 articles that were retrieved, 20 were included in the meta-analysis; four were apelin studies [4,6,7,11], nine were chemerin studies [5,8,15,16,[23][24][25][26][27], five were omentin studies [28][29][30][31][32], one study involved both apelin and omentin [12], and one study involved both chemerin and omentin [33]. The 20 studies enrolled 2981 participants, of which 1493 were GDM patients and 1488 were healthy pregnant women (controls) [4-8, 11, 12, 15, 16, 23-33] (Fig.…”
Section: Literature Research and Characteristics Of The Included Studiesmentioning
confidence: 99%
“…Kaygusuz et al proved that serum visfatin concentration is significantly higher in GDM and is correlated with ferritin levels [29]. Gorkem et al, did not find any difference in visfatin serum levels among healthy pregnant and the ones with GDM [30].…”
Section: Nampt and Gdmmentioning
confidence: 97%
“…There is almost an equal number of studies on circulating maternal visfatin concentrations presenting up-regulation [15][16][17][18][19], down-regulation [20][21][22][23] as well as no influence on GDM development, as compared to the control group [24]. First studies on the relationship between the concentrations of NAMPT and prevalence of GDM were reported 10 years ago.…”
Section: Nampt and Gdmmentioning
confidence: 99%
“…Indeed, visfatin appears to be involved in glucose metabolism regulation and IR, suggesting its role in GDM pathogenesis 59 . Research reports have shown increased levels of circulating visfatin in pregnancies complicated with GDM 36,54,58,61,79 . The reason why women with increased BMI are at greater risk of developing GDM is related to an increase in IR.…”
Section: Visfatin and Obesity‐related Pregnancy Complicationsmentioning
confidence: 99%